Content analysis of educational videos on hand hygiene during COVID-19 pandemic - Divya Verma; Divita Sharma; Meenakshi Khapre (Wolters Kluwer Medknow Publications, 2021)
BACKGROUND: Online platforms are the most popular mode of entertainment, simultaneously imparting knowledge and education. During COVID pandemic, there was a sudden influx of educational videos on social media/websites with a purpose of spreading the information about hand hygiene (HH) practices. The aim of this study was to explore and assess the HH videos based on its content and technical quality to promote the learning experience of videos. MATERIALS AND METHODS: HH videos from the official sites of five international health organizations and 42 national health institutes were assessed based on their availability of the HH videos. Verified YouTube videos on HH since January 2020 were further screened and assessed using the author's designed validated checklist. Each video was systematically evaluated and scored against the seven categories, namely introduction, audio, visuals/background, speaker/demonstrator, content, timing, and appeal. RESULTS: A total of 50 videos were assessed for analysis. Of these, 82% of videos scored >50%, i.e., 14. Among low scorer, seven videos were from YouTube channel. Majority of the videos were technically sound, 44% aroused interest, 82% had a simple, understandable message; in around 46% of the videos, the presenter was a healthcare worker; and in 24%, the information was accurate as per the World Health Organization guidelines. CONCLUSIONS: This study concluded that most of the HH videos were found to be just above average in their content quality and technicality.